Antibacterial and antibiofilm activities of aqueous fraction of methanol extract from stem-bark of Parkia biglobosa against chronic wounds’ pathogens - O. Akanni, Ifeoluwa.; Onaolapo, Josiah. A.; O. Bolaji, Rebecca; Danmalam, Habib U.; Udobi, Chinweizu E. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2024)
Background: Biofilm is a 3D structured community of microorganisms usually enclosed in an extracellular polysaccharide matrix and act as a microbial battlefront. They are often polymicrobial and when the associated microorganisms are pathogenic, biofilms become a significant virulence factor and contribute to wound chronicity as well as antibiotic resistance. Methods: The antibiofilm effect of aqueous fraction from stem-bark methanol extract of Parkia biglobosa (Jacq.) R.Br.ex G.Don, also known as the African Locust Bean tree, was determined against biofilm-producing bacteria isolated from chronic wounds of patients in Kaduna, Nigeria. One hundred and sixty-eight bacterial isolates were obtained from chronic wounds samples of patients in four selected health facilities between December 2020 to November 2021. The isolates were identified using standard microbiological methods. Biofilm formation was determined and antibacterial and antibiofilm activities of the aqueous fraction from the stem-bark methanol extract of Parkia biglobosa were investigated using microtitre plate method. Results: 115 (68.5%) isolates were multidrug-resistant (MDR) to the antibiotics tested while 60 (52.2%) of the MDR isolates were biofilm-formers. The fraction was found to possess strong biofilm-inhibiting activity of 76.4%±6.3 against Staphylococcus spp. at half minimum inhibitory concentration (sub-MIC) and 96.8%±0.2 against Proteus spp. at half minimum bactericidal concentration (sub-MBC) and antibiofilm activity against pre-formed biofilms ranged from 74.2%±10.7 against Staphylococcus species, 80.0%±4.4 against Proteus spp. at sub-MIC and 96.7%±0.1 against Pseudomonas spp. at sub-MBC. Conclusion: Aqueous fraction from stem-bark methanol extract of Parkia biglobosa possessed potent biofilm inhibitory and antibiofilm activities thereby providing a potential alternative treatment for bacterial infections.